Isolation and Molecular Identification of Vibrio natriegens from Diseased Portunus trituberculatus in China. Issue 6 (4th July 2016) - Bi, Keran; Zhang, Xiaojun; Yan, Binlun; Gao, Huan; Gao, Xiaojian; Sun, Jingjing
Abstract: In July 2010, heavy mortalities were seen in cultured swimming crabs, Portunus trituberculatus, from Jiangsu Province in China. Two isolates, XA1 and XA2, were isolated from cardiac muscle and somatic muscle of the moribund crabs on ZoBell's marine 2216E agar and were confirmed as the causative agent for the mass mortalities seen on that farm. The morphological and physiological characteristics as well as the biochemical tests of the two isolates were identical and were similar to Vibrio natriegens . Both were gram‐negative, oxidase positive, produced acid when fermenting glucose, and failed to grow in the media containing 1% NaCl. Furthermore, the sequencing of the 16S rRNA, gapA, ftsZ, mreB, and topA genes revealed that the two isolates were identical and had a 0.99 homology coefficient with V. natriegens . The Neighbor‐Joining tree based on the concatenated sequences of four housekeeping genes (gapA, ftsZ, mreB, and topA) strongly supported that XA1 was most closely related to V. natriegens within the Vibrio harveyi –related clade. In addition, pathogenicity testing using immersion challenge confirmed that strain XA1 was virulent to juvenile crabs, and the LD50 value was 1.09 × 10 6 . This is the first report on V. natriegens as a virulent pathogen for Portunus trituberculatus .